G-protein coupled receptors and tau-different roles in alzheimer's disease - Chidambaram, Hariharakrishnan; Chinnathambi, Subashchandrabose (Neuroscience, 2020)
Post-translational modification of Tau, a microtubule-associated protein in the neuronal cell, plays a major role in Alzheimer's disease. Tau is an axonal protein expressed in mature neurons that promote the self-assembly of tubulin into microtubules and its stabilization in neurons. Phosphorylation of Tau makes it prone to aggregation at the intra-neuronal region leading to impaired neurotransmission and dementia. Tau aggregates undergo trans-cellular propagation by the release of fibrillar species into the extra-cellular environment from damaged and infected neurons that can be internalized by neighbouring neuronal and glia cells and promotes aggregation in healthy cells. G-protein coupled receptors, the largest group of seven transmembrane receptors, are involved in neuronal signal transduction in response to various signals such as hormones and neurotransmitters. In Alzheimer's disease, GPCRs are involved in phosphorylation of Tau through various downstream kinases such as GSK-3b, CDK-5 and ERKs signalling cascade. Several neuronal GPCRs that are involved in Tau phosphorylation are elaborated in this review. The astrocytic GPCR, Tau phosphorylation mediated by CaS receptors and its propagation by exosomes are also elaborated. In the microglia, the extra-cellular Tau binding to a chemokine GPCR, CX3CR1 triggers its internalization, whereas Tau phosphorylation at specific sites decreases its binding affinity to this receptor. Here we highlight the role of GPCRs in Tau phosphorylation and Tau interaction in different cells of the nervous system. Hence, the role of GPCRs are attaining more attention in the therapeutic field of Alzheimer's disease. Specific agonists/antagonists and allosteric modulators could be the potential target for therapy against GPCR-mediated Tau phosphorylation in Alzheimer's disease. (C) 2020 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: Alzheimer's disease; GPCRs; microglia; Tau internalization; Tau phosphorylation; Tau propagation

G-protein coupled purinergic P2Y12 receptor interacts and internalizes TauRD-mediated by membrane-associated actin cytoskeleton remodeling in microglia - Chidambaram, Hariharakrishnan; Das, Rashmi; Chinnathambi, Subashchandrabose (European Journal of Cell Biology, 2022)
In Alzheimer’s disease, the microtubule-associated protein, Tau misfolds to form aggregates and filaments in the intra- and extracellular region of neuronal cells. Microglial cells are the resident brain macrophage cells involved in constant surveillance and activated by the extracellular deposits. Purinergic receptors are involved in the chemotactic migration of microglial cells towards the site of inflammation. From our recent study, we have observed that the microglial P2Y12 receptor is involved in phagocytosis of full-length Tau species such as monomers, oligomers and aggregates by actin-driven chemotaxis. This study shows the interaction of repeat-domain of Tau (TauRD) with the microglial P2Y12 receptor and the corresponding residues for interaction have been analysed by various in-silico approaches. In the cellular studies, TauRD was found to interact with microglial P2Y12R and induces its cellular expression confirmed by co-immunoprecipitation and western blot analysis. Furthermore, the P2Y12R-mediated TauRD internalization has demonstrated activation of microglia with an increase in the Iba1 level, and TauRD becomes accumulated at the peri-nuclear region for the degradation. Similarly, immunofluorescence microscopic studies emphasized that TauRD is phagocytosed by microglial P2Y12R via the membrane-associated actin remodeling as filopodia extension. Upon internalization, we have demonstrated the P2Y12R signaling-mediated degradation of accumulated TauRD by lysosomal pathway. Altogether, microglial P2Y12R interacts with TauRD and mediates directed migration and activation for its internalization and degradation.
Keywords: Alzheimer’s disease; Internalization; microglia; P2Y12R; Phagocytosis; Tau

G-protein coupled purinergic P2Y12 receptor interacts and internalizes Tau(RD)-mediated by membrane-associated actin cytoskeleton remodeling in microglia - Chidambaram, Hariharakrishnan; Das, Rashmi; Chinnathambi, Subashchandrabose (European Journal of Cell Biology, 2022)
In Alzheimer's disease, the microtubule-associated protein, Tau misfolds to form aggregates and filaments in the intra- and extracellular region of neuronal cells. Microglial cells are the resident brain macrophage cells involved in constant surveillance and activated by the extracellular deposits. Purinergic receptors are involved in the chemotactic migration of microglial cells towards the site of inflammation. From our recent study, we have observed that the microglial P2Y12 receptor is involved in phagocytosis of full-length Tau species such as monomers, oligomers and aggregates by actin-driven chemotaxis. This study shows the interaction of repeat-domain of Tau (Tau(RD)) with the microglial P2Y12 receptor and the corresponding residues for interaction have been analysed by various in-silico approaches. In the cellular studies, Tau(RD) was found to interact with microglial P2Y12R and induces its cellular expression confirmed by co-immunoprecipitation and western blot analysis. Furthermore, the P2Y12R-mediated Tau(RD) internalization has demonstrated activation of microglia with an increase in the Iba1 level, and Tau(RD) becomes accumulated at the peri-nuclear region for the degradation. Similarly, immunofluorescence microscopic studies emphasized that Tau(RD) is phagocytosed by microglial P2Y12R via the membrane-associated actin remodeling as filopodia extension. Upon internalization, we have demonstrated the P2Y12R signaling-mediated degradation of accumulated Tau(RD) by lysosomal pathway. Altogether, microglial P2Y12R interacts with Tau(RD) and mediates directed migration and activation for its internalization and degradation.
Keywords: Alzheimer's disease; Internalization; microglia; P2Y12R; Phagocytosis; Tau(RD)